Respuesta :
Answer:
Step-by-step explanation:
Task 1:
Non linear systems of equations:
x + y = 1 -------------------(I) {Linear equation}
y = 1 - x
y = x² - 5 ---------------(II) {Quadratic equation}
Substitute y =1 - x in equation (II)
(II) --> 1 -x = x² -5
Add 'x' to both sides
1 = x² + x - 5
0 = x² + x - 5 - 1 {Subtract 1 from both sides}
x² + x - 6 = 0
x² + 3x - 2x - 6 = 0 {Rewrite the middle term}
x( x + 3) - 2(x + 3) = 0
(x + 3)(x - 2) = 0
x + 3 = 0 ; x - 2 = 0
x = - 3 ; x = 2
When x = - 3 , y = 1 -(-3 )
= 1 + 3
y = 4
When x = 2 ; y = 1 - 2 = -1
Solution of the equations: (-3,4) & ( 2,-1)
Task 2:
Part 1: x = 40 ; y = 30
(x - y)² = x² - 2xy + y²
(40 - 30)² = 40² - 2*40*30 + 30²
= 1600 - 2400 + 900
= 2500 - 2400
= 100
Part 2:
a = 10 , b = 11
a³ + b³ = (a + b)(a² - ab +b²)
(10)³ + (11)³ = (10 +11)(10² -10*11 + 11² )
= 21* (100 - 110 + 121)
= 21 * ( 221 - 110)
= 21 * 111
= 2331